2009
DOI: 10.2334/josnusd.51.223
|View full text |Cite
|
Sign up to set email alerts
|

Radiopacity of conventional, resin-modified glass ionomer, and resin-based luting materials

Abstract: Abstract:The purpose of the present study was to evaluate the radiopacity of currently available dental luting materials. Five conventional cements, six resinmodified glass ionomers (RMGIs), two methyl methacrylate (MMA)-based acrylic resins (eight shades), and nine composite luting materials were evaluated. Radiographs of the specimens were taken together with tooth slices and aluminum step wedges. The density of the specimens was determined with a densitometer and was expressed in terms of the equivalent thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 10 publications
6
33
0
14
Order By: Relevance
“…To overcome this deficiency, radiopaque secondary fillers have been added (25)(26)(27). In the present study, Equia Fil showed significantly higher radiopacity values than GCP Glass Fill.…”
Section: Discussionmentioning
confidence: 72%
“…To overcome this deficiency, radiopaque secondary fillers have been added (25)(26)(27). In the present study, Equia Fil showed significantly higher radiopacity values than GCP Glass Fill.…”
Section: Discussionmentioning
confidence: 72%
“…In dental cements, radiopacity depends on the selection of the polymer matrix, the type and proportion of radiopaque filler, its size, density, and addition level (38). The filler particles of magnesium oxide, zinc oxide, fluoroaluminosilicate glass, strontium, barium, and zirconium give the radiopaque property to polycarboxylate, zinc phosphate, and glass ionomer cements.…”
Section: Dental Cementsmentioning
confidence: 99%
“…The filler particles of magnesium oxide, zinc oxide, fluoroaluminosilicate glass, strontium, barium, and zirconium give the radiopaque property to polycarboxylate, zinc phosphate, and glass ionomer cements. The atomic numbers of the elements of aluminum, silicon, calcium, zinc, strontium, zirconium, and barium are 13,14,20,30,38,40, and 56, respectively. The radiopacity of a material increases alongside an increase in the particle ratio of those materials which have an element content with a high atomic number.…”
Section: Dental Cementsmentioning
confidence: 99%
“…Quanto mais alto o número atômico do elemento presente na composição do material, maior radiopacidade deve ser observada 17,24 .…”
Section: Discussionunclassified